Playing with Leviathan : interpretation and reception of monsters from the biblical world - Bekkum, K. van. (Themes in Biblical Narrative, 2017)
Since ancient times Leviathan and other monsters from the biblical world symbolize the life-threatening powers in nature and history. They represent the dark aspects of human nature and political entities and reveal the supernatural dimensions of evil. Ancient texts and pictures regarding these monsters reflect an environment of polytheism and religious pluralism. Remarkably, however, the biblical writings and post-biblical traditions use these venerated symbols in portraying God as being sovereign over the entire universe, a theme that is also prominent in the reception of these texts in subsequent contexts. This volume explores this tension and elucidates the theological and cultural meaning of 'Leviathan' by studying its ancient Near Eastern background and its attestation in biblical texts, early and rabbinic Judaism, Christian theology, Early Modern art, and film.